Interactions between water, soil and forest health in lowland tropical forests - Lion, Marryanna; Mohd Razali, Sheriza (International Journal of Agriculture, Forestry and Plantation, 2023)
The severe drought that hit Malaysia was caused by the El-Niño Southern Oscillation (ENSO). Studies have shown that tropical forests depend heavily on evapotranspiration during the dry season, which is influenced by factors such as rainfall quantity and vapour pressure deficit (VPD). The objective of this research is to investigate the interaction between soil, water and forest health by measuring water content and evapotranspiration. The research aimed to understand how the forest ecosystem responds to severe dryness by monitoring soil water content and evapotranspiration, comparing them to rainfall and VPD during the research period. Forest health was determined by satellite indices such as the Normalized Difference Vegetation Index (NDVI) and soil moisture index (SMI). The study took place at the Pasoh Forest Reserve (FR) in Jelebu, which has the lowest annual rainfall, making it an ideal location to study the potential effects of climate change on the forest ecosystem. The results revealed that the forest's evapotranspiration uses a significant amount of rainfall in Pasoh, while less than 10 helps replenish the soil's water content. Due to the high intensity and brief duration of rainfall, between 20 and 45 of it contributes to surface runoff. Despite a consistent VSWC pattern throughout the observation period, the observation in 2019 and 2020 demonstrates that the forest in Pasoh FR responded favourably to the amount of rainfall. Several dry spells with very low monthly rainfall (less than 60 mm per month) were recorded in 2019. February 2019 was one of the driest months on record, with only 3.56 mm of rain falling. January 2022 was also classified as dry, with less than 60 mm of monthly rainfall. The publication of these findings has significantly enhanced and updated forest hydrology information in this region. This information is vital for improving research ideas and can be utilized for climate change mitigation plans. Understanding how soil moisture and evapotranspiration react to dry conditions in tropical forests is crucial research. It provides valuable insights into the ecosystems' vulnerability to climate change, which can inform adaptive management strategies and ensure long-term resilience and sustainability.